2013
DOI: 10.1016/j.taap.2013.03.023
|View full text |Cite
|
Sign up to set email alerts
|

p53 activation by Ni(II) is a HIF-1α independent response causing caspases 9/3-mediated apoptosis in human lung cells

Abstract: Hypoxia mimic nickel(II) is a human respiratory carcinogen with a suspected epigenetic mode of action. We examined whether Ni(II) elicits a toxicologically significant activation of the tumor suppressor p53, which is typically associated with genotoxic responses. We found that treatments of H460 human lung epithelial cells with NiCl2 caused activating phosphorylation at p53-Ser15, accumulation of p53 protein and depletion of its inhibitor MDM4 (HDMX). Confirming activation of p53, its knockdown suppressed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…An increasing body of evidence indicates that heavy metals and metallic agents may play an important role in tumorigenesis, but direct functional connections with MT2A gene activity, and thus toxicity of metallic elements, remains poorly defined (Ahamed and Alhadlaq, 2014;Akinmoladun et al, 2013;Crisponi, 2014;Rehman and Husnain, 2014;Qiao et al, 2014;Wong et al, 2013). The importance of the relationship between MT2A SNP and aberrant expression of heavy and toxic metals in malignant or benign tumors has been investigated in only a few studies and the relationship itself remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…An increasing body of evidence indicates that heavy metals and metallic agents may play an important role in tumorigenesis, but direct functional connections with MT2A gene activity, and thus toxicity of metallic elements, remains poorly defined (Ahamed and Alhadlaq, 2014;Akinmoladun et al, 2013;Crisponi, 2014;Rehman and Husnain, 2014;Qiao et al, 2014;Wong et al, 2013). The importance of the relationship between MT2A SNP and aberrant expression of heavy and toxic metals in malignant or benign tumors has been investigated in only a few studies and the relationship itself remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have suggested that exposure to nickel soluble and particulate forms may have a carcinogenic potential on the airway epithelium (Ahamed et al, 2014;Forti et al, 2011;Pietruska et al, 2011;Tokar et al, 2011;Wong et al, 2013). A considerable body of evidence exists of the genotoxic and mutagenic activity of Ni ions in human epithelial cells, but the exact mechanisms of nickelinduced tumorigenesis remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations